Four new combinations in the legume genus Brachypterum - Sirichamorn, Yotsawate; Adema, Frits F.A.C.B. (Thai Forest Bulletin (Botany), 2020)
The genus name Brachypterum (Fabaceae) is now conserved against Solori. Four more new combinations in Brachypterum are made for the Chinese B. eriocarpum, the Australian B. involutum, the Indian B. pseudorobustum and the Thai and northern Indo-Chinese B. thorelii. Some morphological information and nomenclatural history of the genus is provided, as well as a distribution map for the four species.